Penyuluhan Penyakit Tidak Menular (Hipertensi) Pada Ibu Hamil Di Kelurahan Bonto Kio Kecamatan Minasatene - Prihatini, Surya; Samila, Samila; Febrianti, Nur; Masdarwati, Masdarwati; Maran, Albertus Ata; Qasim, Muhammad; Alim, Andi; Rambu, Sitti Herliyanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Hypertension in pregnancy can be classified into pre-eclampsia, eclampsia, chronic hypertension in pregnancy, chronic hypertension with preeclampsia and gestational hypertension. The purpose of holding PkM is to increase public awareness of hypertension in order to prevent further complications and prevent an increase in the incidence of hypertension sufferers, especially in pregnant women in Bonto Kio Village, Minasatene District. The method used is the Socialization of Non-Communicable Diseases and Early Detection of Hypertension through the Community Service Team through Socialization Non-communicable diseases are diseases that cannot be transmitted from person to person, whose development progresses slowly over a long period of time (chronic) and health screening is carried out. including blood pressure, blood sugar check, cholesterol check, uric acid check, height, abdominal circumference and weight. If the screening is complete, counseling is given one by one regarding the results of the screening. Therefore it can be concluded that a significant increase is related to knowledge of pregnant women about hypertension and behavior to control blood pressure before and after community service activities in Bonto Kio Village, Minasatene District.